(untitled) (Journal of Fiber Bioengineering and Informatics, 2010)
Well-dispersed multiwalled carbon nanotubes (MWNTs)/polyethylene composites have been prepared from melt blending, and composite fibers were prepared via direct melt extrusion of immiscible blends with CAB and subsequent removal of CAB matrix. Scanning electron microscopy was employed to observe the distribution of the MWNTs in the composites, indicating a nanotube network formed in the matrix. SEM images also investigated that the average diameter of PE/MWNTs nanofibers can be 300-400nm. In addition, the crystalline structures of the CNTs/PE nanofibers were characterized by DSC, WAXD and POM, which show a decrease in the crystallinity of PE due to the addition of MWNTs. The thermal properties of composite fibrils were also modified. This fabrication process possesses features of controllability and is environmental friendly during the manufacture of thermoplastic nanofibers.